Gender Disparity in Literacy and its Rural-Urban Differentials: Block-Wise evidences from Lucknow District, U.P. - Choubey, Alok Kumar; Rai, Gayatri (National Geographical Journal of India, 2022)
Literacy is a multidimensional concept, an important demographic element of human process and progress. It acts as a catalyst for overall development and helps in eliminating gender disparity at all levels.Literacy rate reflects the general achievement of growth for any region. Higher literacy corresponds to better health, higher productivity, high income, improved understanding & capability, better standard of living, lesser exploitation, increased participation in community life and above all consciousness of self. So, being a literate is imperative for a dignified life. Lucknow district exhibits varying levels of literacy among male-female population. The urban-rural contrastalso indicates spatial gender literacy variations. The present paper attempts to highlight and analyse gender disparity in literacy at district level, to identify the rural-urban differentials in literacy achievement of male-female population and its regional variations taking administrative blocks as study units.The study is based on published secondary sources of data collected from District Census Handbook. The methodology adopted for this empirical analysis includes the use of disparity and differential indexes along-with gap analysis. It is believed that the present study will be useful in reflecting geographical variations in gender literacy and may support literacy programmes in study region so as to achieve comprehensive rural-urban gender equality.